2014
DOI: 10.1186/ar4434
|View full text |Cite
|
Sign up to set email alerts
|

Synovial membrane protein expression differs between juvenile idiopathic arthritis subtypes in early disease

Abstract: IntroductionJuvenile idiopathic arthritis (JIA) is the most common rheumatological disease of childhood with a prevalence of around 1 in 1,000. Without appropriate treatment it can have devastating consequences including permanent disability from joint destruction and growth deformities. Disease aetiology remains unknown. Investigation of disease pathology at the level of the synovial membrane is required if we want to begin to understand the disease at the molecular and biochemical level. The synovial membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Using proteomic analyses and immunoassays, signatures of serum proteins that distinguish two clinical phenotypes of SJIA and help differentiate autoinflammatory SJIA from infections were discovered. Proteomics has been relatively underused in paediatric rheumatology with most studies focusing on synovial fluid protein expression in JIA 32 33. Proteomic analyses have, however, identified serum protein profiles of SJIA and revealed biomarkers for monitoring response to therapy in SJIA 28 34.…”
Section: Discussionmentioning
confidence: 99%
“…Using proteomic analyses and immunoassays, signatures of serum proteins that distinguish two clinical phenotypes of SJIA and help differentiate autoinflammatory SJIA from infections were discovered. Proteomics has been relatively underused in paediatric rheumatology with most studies focusing on synovial fluid protein expression in JIA 32 33. Proteomic analyses have, however, identified serum protein profiles of SJIA and revealed biomarkers for monitoring response to therapy in SJIA 28 34.…”
Section: Discussionmentioning
confidence: 99%
“…21 A recent study using synovial biopsies identified synovial protein expression patterns that discriminate between clinical subgroups of early JIA. 31 Synovial biopsies are relatively easy to obtain using AS in JIA and may contribute to understanding the early pathological changes and disease process in JIA. 31 Such studies may identify patients who are at high risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…31 Synovial biopsies are relatively easy to obtain using AS in JIA and may contribute to understanding the early pathological changes and disease process in JIA. 31 Such studies may identify patients who are at high risk of disease progression. Protein modification has been found to be a surrogate marker of uncontrolled inflammation in JIA, and synovial protein analysis could identify patients who are at high risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative proteomic analysis has been a point of discussion for the past few decades and has been applied in various disease areas to understand the dynamics of the organisms' biological system and its proteomic content [124]. Major advances in the development of label-free DDA and DIA approaches over the last decade have demonstrated to help obtain a vast amount of information and almost a complete sense of the true biological state.…”
Section: Mrmmentioning
confidence: 99%